Metal‐Free and Heterogeneous Photocatalytic Reduction of 4‐Nitroaniline by a Poly(Ethylene Glycol)‐Supported Eosin Dye under Visible‐Light Exposure. Issue 14 (26th June 2019) - Chibac, Andreea L.; Melinte, Violeta; Brezová, Vlasta; Renard, Estelle; Brosseau, Arnaud; Langlois, Valerie; Versace, Davy‐Louis
Abstract: A new feasible approach for the photoreduction of a chemical pollutant, 4‐nitroaniline, to p ‐phenylenediamine was developed. We highlighted the crucial roles of a polymer backbone and the atmosphere for the efficient heterogeneous reduction of 4‐nitroaniline. The novel synthesized poly(ethylene glycol)‐derived film containing immobilized eosin dye revealed a high photoreduction rate of 4‐nitroaniline. According to laser flash photolysis results the first step of this photoinduced process represents a single electron transfer from eosin radical anion to the 4‐nitroaniline to form a nitroaniline radical anion. The in‐situ electron paramagnetic resonance spin‐trapping experiments evidenced the generation of superoxide radical anion serving as catalyst in the p‐ phenylenediamine production according to a photoreduction process. The main roles play by poly(ethylene glycol) matrix as efficient reducing agent and hydrogen‐donor molecule was also pointed out. A mechanism was proposed to explain the heterogeneous photoreduction of 4‐nitroaniline to p ‐phenylenediamine in the presence of eosin dye‐based poly(ethylene glycol) system under air. Abstract : Facile photoreduction : A new approach for the photoreduction of 4‐nitroaniline to p ‐phenylenediamine under visible‐light exposure employing a poly(ethylene glycol)‐supported eosin dye film was developed. The novel synthesized poly(ethylene glycol)‐derived film has a high photoreduction rate of 4‐nitroaniline. The poly(ethylene glycol) matrix plays a crucial role as efficient reducing agent and hydrogen‐donor molecule, and the generation of a superoxide radical anion that serves as catalyst was observed.